Rising Sea Levels and Sinking Property Values: The Effects of Hurricane Sandy on New York's Housing Market - Francesc Ortega; Süleyman Taspinar (Institute for the Study of Labor (IZA), 2016)
Are coastal cities adjusting to rising sea levels? This paper argues that large-scale events have the potential to ignite the process. We examine the effects of hurricane Sandy on the New York City housing market. We assemble a large plot-level dataset with rich geographic data on housing sales in New York City for the period 2003-2015, along with information on which building structures were damaged by the hurricane, and to what degree. Our difference-in-difference estimates provide robust evidence of a negative impact on the price trajectories of houses that were directly affected by Sandy. Interestingly, this is also the case for houses that were not damaged but face high risk of coastal flooding. Our results suggest that Sandy has increased the perceived risk of living in those neighborhoods. We also show that the negative effects on housing prices appear to be highly persistent.
Keywords: H56; K42; R33; 330; climate change; real estate; cities; Hurricane Sandy